Evaluating the frequency of Self-Immolation and its Relationship with Social and Demographic Status of the Patients Referring to Ghotboddin E Shirazi during the Years 2006 and 2011 - Mansour Kashfi; Maryam Yazdankhah; Ali Khani jeihooni; mojtaba karimi (Fasa University of Medical Sciences, 2014)
Background & Objective: Suicide is the act of injuring oneself in order to destruct one's life. One of the worst ways to attempt suicide, especially in eastern countries, is self- burning. This study aimed to show the frequency of self- burning and its relationship with social and demographic status.  Materials & Methods: In this cross-sectional study, all medical records of patients who admitted to Ghotbeddin E Shirazi hospital for burns during the years 2006 and 2011 were collected. The data were analyzed by SPSS-16 software, descriptive statistical methods and chi-square tests.  Results: The results showed that from 2071 cases of burn patients admitted to Ghotbeddin E Shirazi Hospital, 439 cases (21.1%) have been caused by self-immolation. The proportion of self-immolation among women was 70.7%, in married was 58.4%, and in rural population was 56.6%. It was most prevalent in the age group of 25-44 years old (47.4%). In most cases, self-immolation was occurred with flammable liquids especially oil and gasoline (71.8% and 17.3%, respectively) and at home (90/8%). 67.8% of cases lead to death. (Case-fatality rate was 67.8%). The most cause of self-immolation attempting was family disputes.  Conclusion: High self-immolation rate in females and the age group of adolescents and youth is significant which should be considered as an important issue in terms of health.